Aplicación de la transformada de wavelet para ubicación de fallas en sistemas eléctricos de potencia - Cruz Andaluz, Luis Rubén (2016)
Generally, faults caused in Electrical Power Systems (EPS) are characterized to be short duration and have large magnitude variations, for this reason if do not take proper corrective actions, these faults could be able to lead an entire collapse of the electrical system. The faults of the transmission lines are often produced by technical and environmental reasons. In this context, the present paper proposes a practical application for the wavelet transform with regard to locate faults in electrical systems, specially applied on transmission lines by using the principle of traveling wave. For that, an application has been developed an application that simulates the determination of the distance to the fault happened. Finally, the result analysis of the three simulations done demonstrates that the wavelet transform has a high grade of reliability to locate faults, and also the sensitivity results in front of changes in the line parameters are showed.